Constructive Journalism and its Kin: A Comparative Matrix Diagram of Emerging Journalistic Practices - Yinglei, HE; Hasan, Nik Norma Nik (Journal of Posthumanism, 2025)
This study provides a systematic review of twelve distinct journalism approaches, centering on constructive journalism. Through an analysis of the academic literature, this paper explores the shared values, distinguishing features, and theoretical frameworks of each approach, including solutions journalism, peace journalism, and slow journalism. A matrix diagram was developed to visually represent these relationships, mapping the approaches along key dimensions such as audience engagement, problem-solving focus, and future orientation. The study highlights constructive journalism as the most comprehensive approach, integrating diverse principles and practices. This comparative analysis offers a new method for understanding and categorizing these approaches, presenting a clearer perspective on how they complement and differ from one another. The findings contribute to the broader discourse on journalistic practices and suggest avenues for future research, including the integration of digital tools and exploration of cultural variations in media application.